Changes in Physico-chemical Attributes of Burmese Grape (Baccaurea sapida Muell. Arg.) during Growth and Development - Bhowmick, Nilesh; Deb, Prahlad; Pradhan, Saurabh (International Journal of Bio-resource and Stress Management, 2023)
Burmese grape or Baccaurea sapida Muell. Arg. is an underutilized fruit crop and it is grown as homestead condition of northern districts of West Bengal. Locally the fruit is called as Latka, or Latkan or Lotko or Notko. Very limited document is available regarding the fruit quality and its changing pattern during fruit growth and development pattern. The present study on developmental pattern of Burmese grape was carried out in respect to different physical and biochemical aspects of fruits on the plants of farmers house hold nearer to the Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, West Bengal. All the plants aged between ten to fifteen years and were well grown, free from pests and diseases. After fruit set, the required fruit bunches were tagged on all sides to obtain uniform result. The fruits were harvested and subjected for studies on physico-chemical changes from 30th days after fruit set and continued up to 86th days after fruit set at weekly interval. Fruit size (length and diameter), juice content increased while peel thickness and seed weight decreased with advancement of maturity. Notable increase in TSS, sugar content and sugar: acid ratio were observed with decrease in acidity. At the time of harvest the fruits have attained TSS around 12.13OBrix, acidity less than 2.16%, 4.18% total sugar and pericarp colour should be yellowish green. Considering the fruit size, fruit weight and all the fruit quality characteristics it is suggested that the Burmese grape can be harvested in between 80-85 days after fruit set for best desert quality.